Context and Implications Document for: Assessment And The Logic Of Instructional Practice In Secondary 3 English And Mathematics Classrooms In Singapore. Issue 1 (13th August 2013) - Hogan, David; Chan, Melvin; Rahim, Ridzuan; Maung, Aye Khin; Chen, Loo Siok; Zhe, Seng Yee; Wenshu, Luo
Abstract : This guide accompanies the following article: David Hogan, Melvin Chan, Ridzuan Rahim, Aye Khin Maung, Loo Siok Chen, Seng Yee Zhe and Luo Wenshu, Assessment And The Logic Of Instructional Practice In Secondary 3 English And Mathematics Classrooms In Singapore, Review of Education, 10.1002/rev3.3002